THE WOMAN STEREOTYPE IN HERCULES AND THE AMAZON WOMAN - Juhridin (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
The writer is interested in choosing the film as the objective of research is because it contains with the issue of gender where a woman is stereotyped as a weak creature.  The woman in this film is always appeared as a servant of a man.  Even a mother should treat her boy as a king.  Besides, based on the title Hercules and the Amazon Women, the term of Amazon is closely related to a woman who loves to fight and she also hates men.The writer uses descriptive qualitative method in analyzing the film.  This method describes and anlayzes the collected data from the film.  The writer takes one issue in the film especially about the stereotype of women.  Then, the writer makes the description about gender stereotyping by showing the pictures, dialogues and viewing the correlation relates to the women stereotype between them all            based on the title Hercules and the Amazon Women, the term of Amazon is closely related to a woman who loves to fight and she also hates men. The women in this film are always appeared as a servant of a man because women put in lower position than a man is. The writer is interested in choosing the film as the objective of research, because it contains with the issue of gender where a woman is stereotyped as a weak creature. In this film, the role of women become no freedom because women are treated as a weak creature, and also women regard as a person who do not has no power and defence of body. The women that were stereotyped as housewives or which reflections of their domestic chore, and all of men regard that the existence of women is an unessential thing. The women only regard as a toy which can be played by men and the thrown away when he bored. Therefore, the woman tries to struggle her right and position of men.